(untitled) (E Global Congress, 2026)
In our country, consistent reforms are being implemented to fundamentally modernize the customs system with the aim of liberalizing the economy, simplifying foreign trade procedures, and supporting entrepreneurial activity. In particular, the Decree of the President of the Republic of Uzbekistan No. PF-57 dated March 25, 2025, “On measures to improve the efficiency of the activities of the state customs authorities” serves as an important legal framework in this regard. In accordance with this document, a comprehensive action plan has been approved to digitalize the activities of customs authorities, as well as to introduce startup projects and artificial intelligence technologies into the sector. Within this framework, the digitalization of customs authorities through the implementation of modern and advanced information and communication technologies in the context of the digital economy has been identified as one of the priority tasks [1].